Sacrifices at the altar of self-transformation. (7th July 2017) - Robertson, Alison; Wildcroft, Theo
Abstract : Within both cultural and academic understandings, conceptions of what pain is and the ways it is experienced are complicated by moral and medical pathologisation. Pain is often defined in a tautological fashion, as physical suffering or discomfort caused by illness or injury. Both the experience of pain and responses to that experience are shaped by context and are subject to forces of ideology. On the edges of religious experience there have always been those who explored pain and suffering as a ritual means or end. This paper examines how some people have negotiated the moral context and medicalisation of pain-filled experience, and why: from the physical alchemy of hatha yoga to body modification, BDSM and other complex behaviours often labelled as 'self-harming'. Using personal accounts of encounters with pain as a guide, we will discuss how physical pain and stress are transformed by context and culture, to either enable or deny personal agency and mind–body integration.